Too Much of a Good Thing? An Evolutionary Theory to Explain the Role of Ceramides in NAFLD - Poss, Annelise M.; Summers, Scott A. (Frontiers in Endocrinology, 2020)
Non-alcoholic fatty liver disease (NAFLD), which ranges from the relatively benign and reversible fatty liver (NAFL) to the more advanced and deadly steatohepatitis (NASH), affects a remarkably high percentage of adults in the population. Depending upon severity, NAFLD can increase one's risk for diabetes, cardiovascular disease, and hepatocellular carcinoma. Though the dominant histological feature of all forms of the disease is the accumulation of liver triglycerides, these molecules are likely not pathogenic, but rather serve to protect the liver from the damaging consequences of overnutrition. While ceramides are far less abundant than triglycerides, they play pivotal roles as signals of nutrient excess that drive the manifestation and progression of NAFL/NASH. They promote lipid uptake into the liver and enhance the storage of fat in this organ. Moreover, they drive cellular events that cause hepatocyte apoptosis and fibrosis. In rodents, blocking ceramide synthesis ameliorates all stages of NAFLD. Furthermore, clinical lipidomic assessments reveal associations between serum and liver ceramides and the severity of NAFLD and its comorbidities diabetes and heart disease. These studies support efforts to develop therapeutic strategies to reduce ceramides to prevent and treat these hepatic manifestations of the metabolic syndrome.